2017
DOI: 10.1038/s41598-017-10906-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acid mutations on the conformational dynamics of amyloidogenic immunoglobulin light-chains: A combined NMR and in silico study

Abstract: The conformational dynamics of a pathogenic κ4 human immunoglobulin light-chain variable domain, SMA, associated with AL amyloidosis, were investigated by 15N relaxation dispersion NMR spectroscopy. Compared to a homologous light-chain, LEN, which differs from SMA at eight positions but is non-amyloidogenic in vivo, we find that multiple residues in SMA clustered around the N-terminus and CDR loops experience considerable conformational exchange broadening caused by millisecond timescale protein motions, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In the case of endogenous proteins synthesized in the ER, we found the recognition motif in the edge strand of certain Ig domains, including those of antibodies. Uniformly, the motif located to regions of Ig domains that are dynamic and relatively unstable (44,45). And given the sheet topology of Ig domains (Fig.…”
Section: Implications For Sensing Misfolded Proteins By Ire1αmentioning
confidence: 99%
“…In the case of endogenous proteins synthesized in the ER, we found the recognition motif in the edge strand of certain Ig domains, including those of antibodies. Uniformly, the motif located to regions of Ig domains that are dynamic and relatively unstable (44,45). And given the sheet topology of Ig domains (Fig.…”
Section: Implications For Sensing Misfolded Proteins By Ire1αmentioning
confidence: 99%
“…45,90 As recently reported, increasing the conformational flexibility of the LC, regardless of the impact on its thermodynamic of folding, is another way by which somatic mutations can promote amyloid aggregation. 91,92 It has also been found that somatic mutations that disrupt the LC dimer interface and shift the equilibrium toward the less thermodynamically stable monomeric LC, have the potential to favor amyloidogenesis. 84,93,94 Because association into a stable dimer protects LC from aggregation, 89,[94][95][96][97] pharmacologic stabilization the LC dimer has been proposed as an potential therapeutic strategy for AL-Am amyloidosis.…”
Section: Contribution Of the Somatic Mutationsmentioning
confidence: 99%
“…Various molecular properties of the light chains, such as thermal stability [9,[14][15][16][16][17][18][19] tendency to dimerize [20][21][22] and the dimer interface [23], or protein dynamics [14,24], have been proposed to correlate with their deposition as amyloid fibrils. However, some findings are contradictory, for instance the reports that dimeric LCs are more often found in AL patients [20,22] versus those that the monomeric state is more critical for fibril formation [21] and that stable dimers can even inhibit the aggregation [25].…”
Section: Introductionmentioning
confidence: 99%